Persepsi Masyarakat Kecamatan Telaga Kabupaten Gorontalo Tentang Pantangan Perkawinan Pada Bulan Tertentu - Mustapa, Ira Suryani; Darwis, Rizal; Faisal, Ahmad (Al-Mizan (e-Journal), 2024)
This study aims to determine the perception of the community in Telaga District, Gorontalo Regency about the form of abstinence in carrying out marriages in certain months. This research is a field research with data collection methods such as interview, questionnaire, and documentation. The use of interviews with traditional leaders, religious leaders, academics and the community. The data that has been collected is analysed with descriptive qualitative. The results showed that the existence of good day dating still exists and is so attached to the people of Telaga Subdistrict. They still believe and maintain the habits of their parents. The majority of the people of Telaga Subdistrict believe that marriage in a certain month that is allowed contains sacredness and goodness, but if the marriage is carried out in a certain month that is prohibited it will get disaster. The implementation of this tradition is a form of devotion and respect for ancestors, as well as an effort to create a marriage and household that is sakinah, mawaddah warahmah as mandated by Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law.